2010
DOI: 10.1016/j.physleta.2010.03.019
|View full text |Cite
|
Sign up to set email alerts
|

New Kochen–Specker sets in four dimensions

Abstract: We show that all possible 388 4-dim Kochen-Specker (KS) (vector) sets (of yes-no questions) with 18 through 23 vectors and 844 sets with 24 vectors all with component values from {-1,0,1} can be obtained by stripping vectors off a single system provided by Peres 20 years ago. In addition to them, we have found a number of other KS sets with 22 through 24 vectors. We present the algorithms we used and features we found, such as, for instance, that Peres' 24-24 KS set has altogether six critical KS subsets.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
81
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(81 citation statements)
references
References 33 publications
(53 reference statements)
0
81
0
Order By: Relevance
“…However, we also found KS sets that were not subsets of the 24-24 set (e.g., the 22-11 one, shown in Fig. 3(a) of [31]) and those subsets have the components from a wider set of values (see Table 2 of [31] for the aforementioned 22-11 set). That indicated that there is another class or other classes which contain those sets or both kinds of sets and we started stripping master sets meanwhile discovered [8,37,47,49,50].…”
Section: Tentative 24-24 Class Of 4-dim Ks Sets; Generation Of Kmentioning
confidence: 78%
See 4 more Smart Citations
“…However, we also found KS sets that were not subsets of the 24-24 set (e.g., the 22-11 one, shown in Fig. 3(a) of [31]) and those subsets have the components from a wider set of values (see Table 2 of [31] for the aforementioned 22-11 set). That indicated that there is another class or other classes which contain those sets or both kinds of sets and we started stripping master sets meanwhile discovered [8,37,47,49,50].…”
Section: Tentative 24-24 Class Of 4-dim Ks Sets; Generation Of Kmentioning
confidence: 78%
“…# $ % & ' ( ) * -/ : ; < = > ? @ [ ]ˆ_ ' { | }~ [31]. When all these characters are exhausted we reuse them so as to prefix them by '+', then by '++', and so on.…”
Section: Ks Sets Mmp Hypergraphs Formalism Algorithms and Promentioning
confidence: 99%
See 3 more Smart Citations